2004
DOI: 10.4141/a03-068
|View full text |Cite
|
Sign up to set email alerts
|

Study of carcass, organ, muscle, fat tissue weight, and concentration in rats fed CLA or its precursors by principal component analysis

Abstract: He, M. 2004. Study of carcass, organ, muscle, fat tissue weight, and concentration in rats fed CLA or its precursors by principal component analysis. Can. J. Anim. Sci. 84: 537-543. Carcass, organ and muscle weight, and fat tissue data were obtained from 30 weaned male Wistar rats fed one of three diets, (10 rats/diet) over a period of 60 d. The diets were base with synthetic conjugated linoleic acid (CLA), sunflower oil or beef enriched CLA. The CLA diet contained the base diet and 18.2 g kg -1 of synthetic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This is the first study, to our knowledge, to investigate the effect of supplemental CLA on organ weight and carcass composition in lactating ruminants. In nonlactating laboratory animals, some studies in rats (37) have indicated an increase in internal body organ weight following CLA supplementation, whereas in mice (38,39) and hamsters (17), the increase appears to be mainly in the liver. There is, however, no evidence from the current study that CLA supplementation for 10 wk at doses that caused MFD had any effect on organ weight in lactating ewes.…”
Section: Discussionmentioning
confidence: 94%
“…This is the first study, to our knowledge, to investigate the effect of supplemental CLA on organ weight and carcass composition in lactating ruminants. In nonlactating laboratory animals, some studies in rats (37) have indicated an increase in internal body organ weight following CLA supplementation, whereas in mice (38,39) and hamsters (17), the increase appears to be mainly in the liver. There is, however, no evidence from the current study that CLA supplementation for 10 wk at doses that caused MFD had any effect on organ weight in lactating ewes.…”
Section: Discussionmentioning
confidence: 94%